A facile one-pot hydrothermal synthesis of branched α-MnO2 nanorods for supercapacitor application. Issue 31 (21st August 2015) - Su, Xiaohui; Yang, Xianfeng; Yu, Lin; Cheng, Gao; Zhang, Huanhua; Lin, Ting; Zhao, Feng-Hua
<x xml:space="preserve">Abstract</x> Branched α-MnO2 nanorods are synthesized using a facile, green and effective one-pot hydrothermal approach without surfactants or templates. The branched α-MnO2 nanorod electrode exhibited good supercapacitive properties due to its novel textural morphology and crystal structure.